1975
DOI: 10.1111/j.1348-0421.1975.tb00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Immunological Studies on the Cell Walls of Propionibacterium acnes Strain C7 and Corynebacterium parvum ATCC 11829

Abstract: The chemical and immunological properties of the cell walls prepared from the cells of anaerobic coryneforms, Propionibacterium acnes C7 and Corynebacterium parvum ATCC 11829, were partially investigated. The cell walls prepared from P. acnes C7 and C. parvum ATCC 11829 were composed of fatty acids, polysaccharides consisting glucose, galactose and mannose and mucopeptides consisting mainly of alanine, glutamic acid, a, ε‐diaminopimelic acid, glycine, muramic acid and glucosamine. As the fatty acid constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Recent chemical studies on the cellular constituents of anaerobic coryneforms indicated that such organisms contain some combination of galactose, glucose or mannose as cell wall sugars and alanine, glutamic acid, glycine and diaminopimelic acid as amino acids of peptidoglycan [25]. According to Azuma et al [5], the cell walls of P. acnes C-7 and C. parvum ATCC 11829 were composed of a polysaccharide moiety and a mucopeptide moiety, and contained small …”
Section: Discussionmentioning
confidence: 99%
“…Recent chemical studies on the cellular constituents of anaerobic coryneforms indicated that such organisms contain some combination of galactose, glucose or mannose as cell wall sugars and alanine, glutamic acid, glycine and diaminopimelic acid as amino acids of peptidoglycan [25]. According to Azuma et al [5], the cell walls of P. acnes C-7 and C. parvum ATCC 11829 were composed of a polysaccharide moiety and a mucopeptide moiety, and contained small …”
Section: Discussionmentioning
confidence: 99%
“…In our previous papers, it was shown that the cell walls of P. acnes, P. granulosum, and P. avidum are adjuvants and antitumor agents (5), and that the peptidoglycan of P. acnes plays an important role in these biological activities (9).Recently, the anaerobic "Corynebacterium" species were classified as Propionibacterium (4,8), and a few studies on the biochemical taxonomy of Propionibacterium were carried out (II, 12). We have reported that the peptidoglycan of P. acnes contains glycine in two different linkages, and should be classified as a new type (9).…”
mentioning
confidence: 99%
“…Recently, the anaerobic "Corynebacterium" species were classified as Propionibacterium (4,8), and a few studies on the biochemical taxonomy of Propionibacterium were carried out (II, 12). We have reported that the peptidoglycan of P. acnes contains glycine in two different linkages, and should be classified as a new type (9).…”
mentioning
confidence: 99%
“…Dawes, Tuach and McBride (1974) and McBride, Dawes and Tuach (1976) parvum-derived lipids that had stimulatory and chemotactic properties. Finally, Millman, Scott and Halbherr (1977) partially purified an RNA-containing fraction from the cytoplasm of C. parvum that had anti-tumour properties.It is generally accepted that isolated cell walls or cell-wall fractions resulting from mechanical disintegration, phage-treatment or autolysis of C. parvum cells at best retain only part of the stimulatory activity of the whole cells and, at worst, may be totally inactive (Prkvot et al, 1968;Adlam, Reid and Torkington, 1975;Azuma et al 1975;Millman et al, 1977).In a more recent study, Riveros-Moreno. Bomford and Scott (1978) found that the residual anti-tumour activity of cell walls derived from disrupted C. parvum cells was due to "non specific" macrophage-activation effects; attempts to restore full stimulatory activity to the cell-wall preparations by emulsifying them in oil or attaching them to oil droplets were unsuccessful.…”
mentioning
confidence: 99%
“…It is generally accepted that isolated cell walls or cell-wall fractions resulting from mechanical disintegration, phage-treatment or autolysis of C. parvum cells at best retain only part of the stimulatory activity of the whole cells and, at worst, may be totally inactive (Prkvot et al, 1968;Adlam, Reid and Torkington, 1975;Azuma et al 1975;Millman et al, 1977).…”
mentioning
confidence: 99%